Study Of Rubber Growth Under Constraint of Pyrite In Tidal Swampy Area - Charlos Togi Stevanus; Umi Hidayati; Thomas Wijaya; Andi Nur Cahyo (Center for Journal Management and Publication, 2017)
Muara Sugihan is one of the tidal swamp areas for rubber plant cultivation in South Sumatera. A preliminary survey of the land suitability in 2012 described that there are two main problems, the shallow groundwater problem and low pH (2,87-3,05) between 40-100 depth that indicates the presence of pyrite layers. In the prior of planting, the water drainage has been done to maintain the water table. However, the water drainage was excessive so that water table reach 66 cm from soil surface hence aerobic condition resulted in oxidation of pyrite layer. The method used in this study was survey method consist of measuring the girth of 2 years old rubber plants and sampling of soil, leaves, and water on the trench and the river which indicated the presence of pyrite layers on tidal swamp area, Muara Sugihan. The result showed that the growth of the rubber plants was inhibited, where the girth was 10 cm, while on optimal dry land they normally reached 18 cm. Leaf nutrient analysis showed there was deficient of P, K, and Zn, while on soil analysis showed a low P content. The pyrite was leach from the soil and accumulate into water drainage will lead to low pH of water. This problem can be solved by water management improvement.Â